Rinsing of oropharynx and storage place of respiratory medicine inhaler: A cross‐sectional audit. (1st April 2019) - Okauchi, Shinichiro; Kinoshita, Kensuke; Sato, Shinya; Osawa, Hajime; Yamada, Hideyasu; Miyazaki, Kunihiko; Satoh, Hiroaki; Hizawa, Nobuyuki; Kobayashi, Hiroyuki
Abstract: Background: In patients with bronchial asthma and those with chronic obstructive pulmonary disease (COPD), inhalation therapy and rinsing of the mouth and the oropharynx by gargling ("RMOG") after inhalation are recommended. We performed a cross‐sectional audit aimed at investigating (a) the proportion of patients performing "RMOG" after inhalation and (b) storage place of patients' inhaler. Methods: Patients with bronchial asthma and those with COPD were asked by medical aids at outpatient visits whether they did "RMOG every time, " "RMOG sometimes, " or "no RMOG" after inhalation, and where they stored their inhaler. Results: During a six month study period up to September 2017, 330 consecutive patients with asthma and those with COPD were included in the study. Two hundred and thirty‐two (70.3%) of the 330 patients answered "RMOG every time" and 98 (29.7%) of them did "RMOG sometimes" and did "no RMOG." There was a difference in the proportion of patients performing RMOG after inhalation with patient age. With regard to the storage location of inhaler, we found the proportion of patients performing RMOG was higher in those who stored inhalers in a room with running water than in those who stored inhalers at other places. This difference was found in patients with both bronchial asthma and those with COPD. Conclusions: Further implementation of "patient education" on performing RMOG after inhalation for patients receiving inhaled medication is still necessary. Our results suggest that it is better to store inhalers in places where there is easy access to tap water used for RMOG. Abstract : Rinsing of the mouth and the oropharynx by gargling (RMOG) after inhalation for patients receiving inhaled medication is still necessary. Our results suggested that it is better to store inhaler in places where easy to access tap water used for RMOG.